First order magnetic transition and magnetoelastic effects in Sm2IrIn8 - Lora-Serrano, R.; Correa, V. F.; Adriano,C.; Giles, C.; Duque, J.G.S.; Granado, E.; Pagliuso, P.G.; Murphy, T.P.; Palm, E.C.; Tozer, S.W.; Lacerda, A.H.; Sarrao, J.L.; et al. (Elsevier, 2008)
Correa, V. F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Florida State University; Estados Unidos